2017
DOI: 10.1016/j.omtn.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Dual Tumor-Targeting Nanocarrier System for siRNA Delivery Based on pRNA and Modified Chitosan

Abstract: Highly specific and efficient delivery of siRNA is still unsatisfactory. Herein, a dual tumor-targeting siRNA delivery system combining pRNA dimers with chitosan nanoparticles (CNPPs) was designed to improve the specificity and efficiency of siRNA delivery. In this dual delivery system, folate-conjugated and PEGylated chitosan nanoparticles encapsulating pRNA dimers were used as the first class of delivery system and would selectively deliver intact pRNA dimers near or into target cells. pRNA dimers simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Other organic anti- c-myc nano delivery systems reported are often complex polymer- and peptide-based nanocomposites. Folate-targeted, pegylated chitosan nanoparticles were used to encapsulate anti- c-myc siRNA associated with packaging RNA, to give a dual-targeting anti-tumor system that improved cellular uptake, gene silencing, and cancer cell death [ 67 ]. As a further example, Raichur et al [ 68 ] used a layer-by-layer approach to associate anti- c-myc siRNA with poly(lactic-co-glycolic acid) hollow nanoparticles.…”
Section: Anti- C-myc -Sirnamentioning
confidence: 99%
“…Other organic anti- c-myc nano delivery systems reported are often complex polymer- and peptide-based nanocomposites. Folate-targeted, pegylated chitosan nanoparticles were used to encapsulate anti- c-myc siRNA associated with packaging RNA, to give a dual-targeting anti-tumor system that improved cellular uptake, gene silencing, and cancer cell death [ 67 ]. As a further example, Raichur et al [ 68 ] used a layer-by-layer approach to associate anti- c-myc siRNA with poly(lactic-co-glycolic acid) hollow nanoparticles.…”
Section: Anti- C-myc -Sirnamentioning
confidence: 99%
“…Aptamers are also considered as highly specific and efficient delivery agents for siRNA. A dual tumor-targeting siRNA delivery system combining pRNA dimers with chitosan nanoparticles was designed by Li et al [159]. In this nanovehicle, folate-conjugated and PEGylated chitosan nanoparticles encapsulating pRNA dimers were used.…”
Section: Targeting Moietiesmentioning
confidence: 99%
“…Both in vitro treatment of MCF-7 cells and in vivo treatment of MCF-7 tumor-bearing mice with aptamer-decorated chitosan NPs resulted in increased cellular uptake, stronger cell cytotoxicity, higher cell apoptosis, and more efficacious gene silencing. Higher accumulation of siRNA in the tumor site, stronger tumor inhibition, and longer circulating time were also observed [159] by using this nanocarrier. To deliver P-gp-targeted siRNA into breast cancer cells, Powell et al constructed aptamer-functionalized nanoliposomes.…”
Section: Targeting Moietiesmentioning
confidence: 99%
“…The pRNA-siRNA-aptamer was encapsulated in folate and PEG functionalized chitosan nanoparticles. In that study, the aptamer used was FB4 for a transferrin domain, and the siRNA was c-myc [33]. Wu et al demonstrated that functionalized cationic nanobubbles decorated with PSMA aptamers are able to carry and deliver FoxM1 siRNA to prostate cancer positive cells and xenographic tumors [34].…”
Section: Aptamer In the Delivery Of Therapeutic Nanoparticles Containmentioning
confidence: 99%